MAKING WHITE LIVES: NEGLECTED MEANINGS OF WHITENESS FROM APARTHEID SOUTH AFRICA - Ratele, Kopano; Laubscher , Leswin Laubscher (PINS-Psychology in Society, 2025)
In South Africa, as in other parts of the world, where race was positioned as the fulcrum on which power balances, whiteness seems to have maintained its defining weight. Even after dramatic political changes, whiteness in South Africa seems to continue to determine privilege and desirability. In this article, which analyses material from two archival sources, we consider some of the meanings of, and processes that went into, whiteness as a dominant category of identity and white life as desirable standard. The narratives and cases selected for analysis are not representative of the universe of meaning vis-à-vis whiteness, but are taken to be instructive as to how we might go about looking at whiteness as critical readers and psychologists sensitive to historical, economic and socio-political contexts. In an effort to complicate notions of privilege, dominance and whiteness – and to do so by means of an archive, with sensitivity to dynamics broader than the economic or the structural – the article focuses on the historical constitution and habitation of whiteness in South Africa to uncover and articulate some neglected meanings of whiteness, then and now. The stories of whiteness and white life under apartheid illustrate how these dynamics were fixed in place, insinuated into daily life, and defended against other forms of racial being. At the same time, the article shows how constructions of whiteness and being White were, and continue to be, driven by contradictions, ambiguities and paradoxes. From these stories we note the dynamics and tensions between essence and appearance. They reveal some of the thoughts and feelings that went into making and inhabiting a South African whiteness, and help us understand the complex and nuanced specificities of whiteness in this society.